Developing and implementing performance measurement tools for secondary school / Fatimah Abd Rauf, Radiah Othman and Siti Maznah Mohd Ariff - Abd Rauf, Fatimah; Othman, Radiah; Mohd Ariff, Siti Maznah (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2010)
School Performance Index (SPin) is an alternative measurement tool proposed to measure schools' performance in Malaysia. SPIn in this study has been extended to 161 secondary schools in the state of Selangor. For SPIn to be adopted as a tool to measure performance of secondary school, seven education criteria for performance excellence were incorporated. The criteria include leadership(LD), measurement, analysis & knowledge management(MAKM), strategic planning(SP), students and stakeholders(SS), process management(PM), school and staff focus(SSF), and PMR examination result with the premise that an excellent school should excel in all processes in providing education to their students and not necessary be judged solely on the examination results. The results prove that schools that performed well in PMR do not necessary excel in LD, MAKM, SP, PM, SS and SSF. Also the dimension with the highest mean SPin is SS, followed by PM, MAKM, SSF, SP and lastly, LD. It can safely be concluded that the majority of schools place high importance on students and stakeholders and all processes involved as compared to strategic planning and leadership. This might be due to the fact that Malaysian schools are regulated by the Ministry and they do not compete openly in the market like the private schools. However, in order to achieve the mission of becoming the education hub in the world, these two criteria might be worth considered for. Analysis by District shows that there is not much difference in the overall SPIn for the majority of the school except for the district of Petaling in which the overall SPIn is the lowest. Schools from the districts of Kuala Langat, Sepang and Sabak Bernam are the main frontrunners for best overall performance. The results also show that on the average schools in both urban and rural areas are still lacking in communication and organizational performance, especially, in vision and values. There is no difference in terms of governance and social responsibilities between urban and rural schools, but the leadership of rural schools has better ethical practices as compared to urban schools.